Guys and dolls [videorecording (DVD)] - Brando, Marlon; Sinatra, Frank, 1915-1998; Simmons, Jean, 1929-2010; Mankiewicz, Joseph L.; Mankiewicz, Joseph L.; Runyon, Damon, 1880-1946; Swerling, Jo, 1897-1964 (MGM Home Entertainment, 2000)
A gentleman-gambler falls in love with a missionary, while a floating crap-game operator avoids marriage to his long-time fiancee.